THE FACTORS STIMULATION ATTENTION OF STUDENT IN WEBCASTING SYSTEM - NOVAK, Milan (Journal of Technology and Information Education, 2010)
The article interoduces basic separation of factors stimulating attention of students when using webcasting systems in their study. This factors and their interlacing would had be taken into account when finding of acceptable conception for personal development or buy this system and ensuing integration into learning surfaces in educational institutions.
Keywords: webcasting; education; audio; video; learning object; educational system